Weather-resistant and stain-resistant finishing paint coating for wind power equipment and preparation method thereof

By using a weather-resistant and anti-fouling topcoat coating containing a variety of high-performance components, the problem that wind power equipment coatings are difficult to meet higher usage needs in terms of weather resistance and pollution resistance is solved, and the service life of the equipment is extended and maintenance costs are reduced. effect.

CN119432174AActive Publication Date: 2025-02-14CHINA PAINT MFG CO SHENZHEN
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411588240.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-14
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

Existing wind power equipment coatings are difficult to meet higher usage needs in terms of weather resistance and pollution resistance, resulting in shortening the service life of the equipment and high maintenance costs in harsh environments.

Method used

A kind of fluorocarbon resin, silicone modified acrylic resin, C8-18 fluoroalcohol phosphate, C30-45 alkyldimethylsilyl polypropylene silsesquioxane, aminosilane coupling agent, cyclic pentapolymer Weather-resistant and anti-fouling topcoat coatings with dimethylsiloxane, lignin nanopowder, titanium dioxide, zinc phosphate, talc powder, silicon micropowder, etc., extend through excellent adhesion, wear resistance, weather resistance and stain resistance Equipment service life.

Benefits of technology

This coating significantly improves the protective performance of the surface of wind power equipment, extends the service life of the equipment, and reduces the frequency and cost of maintenance and repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005124845260000141
    Figure BDA0005124845260000141
  • Figure BDA0005124845260000142
    Figure BDA0005124845260000142
  • Figure BDA0005124845260000151
    Figure BDA0005124845260000151
Patent Text Reader

Abstract

The invention provides a weather-resistant and anti-pollution finish paint for wind power equipment and a preparation method of the weather-resistant and anti-pollution finish paint, and belongs to the technical field of paints.The weather-resistant and anti-pollution finish paint is specially designed for equipment with high requirements for weather resistance and pollution resistance. The coating is prepared from the following components: fluorocarbon resin, organic silicon modified acrylic resin, C8-18 fluoroalcohol phosphate, C30-45 alkyl dimethyl silane polypropyl silsesquioxane, an amino silane coupling agent, cyclopentasiloxane, lignin nano powder, titanium dioxide, zinc phosphate, talcum powder, silica powder and the like. The components are matched for use according to a certain proportion, so that the paint has excellent adhesive force, wear resistance, weather resistance and pollution resistance, the service life of equipment can be effectively prolonged, and the maintenance and repair frequency and cost are reduced. The higher use requirements in the aspects of weather resistance and pollution resistance can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a weather-resistant and anti-fouling topcoat coating for wind power equipment and a preparation method thereof. Background Art

[0002] As the global demand for clean energy continues to grow, wind energy, as a renewable and pollution-free energy source, has been widely developed and utilized. Wind power equipment, as a key device for converting wind energy into electrical energy, operates for a long time in various complex natural environments, which places extremely high demands on the protective coatings of wind power equipment.

[0003] On the one hand, wind power equipment is usually installed in harsh environments such as the wild, coastal, and mountainous areas. In these places, the equipment faces a variety of severe tests. The first is the influence of climatic conditions. The temperature variation range in different regions is extremely large. From extremely cold winters to hot summers, the drastic temperature fluctuations will produce huge stress on the surface coating of the equipment. For example, in the cold northern regions, the winter temperature may be as low as dozens of degrees below zero, while in the hot desert areas, the summer temperature may be as high as 40 or 50 degrees Celsius. This temperature change will cause the coating to expand and contract. If the weather resistance of the coating is insufficient, it is easy to crack and peel off.

[0004] Secondly, strong winds are also a challenge that wind turbines must face. High-speed winds will carry dust, particles, etc. to impact the surface of the equipment. Long-term wind and sand erosion will gradually wear out the coating and reduce its protective performance. In addition, wind turbines in coastal areas will also be eroded by salt spray. The salt in seawater forms salt spray in the air, which will accelerate the corrosion of metals and cause serious damage to the steel structure of the equipment. Without good coatings for protection, the service life of wind turbines will be greatly shortened.

[0005] At present, the existing coatings used in wind power equipment generally have the following problems:

[0006] 1. Weather resistance

[0007] 1. Aging problem: Although existing coatings are weather-resistant to a certain extent, they will gradually age when exposed to outdoor environments for a long time and are affected by ultraviolet rays, temperature changes, humidity and other factors. For example, ultraviolet rays can break the polymer molecular chains in the coating, causing the coating to lose its gloss, become brittle, or even powderize. In areas with large temperature differences, the coating may crack due to uneven thermal expansion and contraction, further reducing its protective performance.

[0008] 2. Limited resistance to wind and sand abrasion: Although some coatings claim to be resistant to wind and sand erosion, the coating will still gradually wear out under the long-term impact of strong winds carrying a large amount of sand and dust. Especially in areas with severe wind and sand, the coating on the surface of wind power equipment may show obvious signs of wear in a relatively short period of time, reducing the protective effect on the equipment.

[0009] 2. Anti-fouling

[0010] 1. Insufficient self-cleaning ability: Existing anti-fouling coatings have limited self-cleaning ability when facing some stubborn stains such as oil stains and bird droppings. These stains will accumulate on the surface of the equipment, not only affecting the appearance, but also reducing the power generation efficiency of the equipment. For example, the acidic substances in bird droppings may corrode the coating, while oil stains will hinder air circulation and affect the heat dissipation performance of the equipment.

[0011] 2. Poor adaptability to different pollutants: The types and degrees of pollutants in different regions vary, and existing coatings are often difficult to adapt to various complex pollution environments. For example, in areas with severe industrial pollution, the air may contain a large amount of acidic gases and particulate matter, which places higher requirements on the anti-fouling performance of coatings.

[0012] The construction and maintenance costs of wind power equipment are high. Once the equipment fails, it is difficult and expensive to repair. Therefore, it is necessary to develop coatings with excellent weather resistance and anti-fouling properties to extend the service life of the equipment, reduce maintenance costs, and provide more reliable protection for the development of the wind power industry. Summary of the invention

[0013] The coatings for existing wind power equipment still have the problem that the weather resistance and anti-fouling properties cannot meet higher usage requirements. The present invention provides a weather-resistant and anti-fouling topcoat coating for wind power equipment and a preparation method thereof. The coating contains fluorocarbon resin, silicone-modified acrylic resin, C8-18 fluoroalcohol phosphate, C30-45 alkyldimethylsilylpolypropylsilsesquioxane, aminosilane coupling agent, cyclopentasiloxane, lignin nanopowder, titanium dioxide, zinc phosphate, talc, silicon micropowder and other ingredients. The components are used in a certain proportion, have excellent adhesion, wear resistance, weather resistance and anti-fouling properties, can effectively extend the service life of the equipment, and reduce the frequency and cost of maintenance and repair. The specific technical scheme is as follows:

[0014] A weather-resistant and anti-fouling topcoat for wind power equipment, the coating comprising the following raw materials in parts by mass: 30 to 40 parts of fluorocarbon resin, 20 to 30 parts of organosilicon-modified acrylic resin, 2 to 3 parts of C8-18 fluoroalcohol phosphate, 3 to 5 parts of C30-45 alkyldimethylsilylpolypropylsilsesquioxane, 1 to 3 parts of aminosilane coupling agent, 3 to 5 parts of cyclopentasiloxane, 1 to 1.5 parts of lignin nanopowder, 15 to 20 parts of titanium dioxide, 5 to 10 parts of zinc phosphate, 5 to 10 parts of talc, 3 to 8 parts of silicon micropowder, 0.5 to 1 part of leveling agent, 0.5 to 1.5 parts of defoaming agent, 0.5 to 1 part of dispersant, 0.5 to 1 part of ultraviolet absorber, 0.5 to 1 part of antioxidant, and 20 to 30 parts of propylene glycol methyl ether acetate.

[0015] In the above coating, the particle size range of the lignin nanopowder is below 1 μm.

[0016] In the above coating, the particle size of the titanium dioxide is in the range of 10 μm to 300 μm.

[0017] In the above coating, the particle size range of the zinc phosphate is below 10 μm.

[0018] In the above coating, the particle size of the talc powder is less than 10 μm.

[0019] In the above coating, the particle size of the silicon micropowder ranges from 0.5um to 50μm.

[0020] In the above coating, the leveling agent is a polyurethane leveling agent, model 2041; the defoaming agent is model DF-2409; the dispersant is model DH-5038; the ultraviolet absorber is model UV-1; and the antioxidant is antioxidant 1010.

[0021] The above-mentioned method for preparing a weather-resistant and anti-fouling topcoat for wind power equipment comprises the following steps:

[0022] S1: mixing zinc phosphate, talcum powder and silicon powder uniformly by air flow according to their weight proportions to obtain mixed powder A;

[0023] S2: Mixing lignin nanopowder and C8-18 fluoroalcohol phosphate according to mass fractions, so that the lignin nanopowder is fully infiltrated with C8-18 fluoroalcohol phosphate, and vacuuming and standing for 10 min to 20 min to obtain a mixture B;

[0024] S3: Add leveling agent, defoamer, dispersant, UV absorber and antioxidant to propylene glycol methyl ether acetate according to mass fractions, mix at 1500r / min~2500r / min for 15min~20min, then add titanium dioxide, mix at 1000r / min~1500r / min for 15min~20min, then add fluorocarbon resin and silicone modified acrylic resin, mix at 800r / min~1000r / min for 20min~30min. min, then add mixed powder A, mix at 800r / min~1000r / min for 15min~20min, then add mixture B, C30-45 alkyldimethylsilylpolypropylsilsesquioxane and cyclopentasiloxane, mix at 800r / min~1000r / min for 10min~15min, finally add aminosilane coupling agent, mix at 800r / min~1000r / min for 10min~15min to obtain coating.

[0025] The present invention provides a weather-resistant and anti-fouling topcoat coating for wind power equipment and a preparation method thereof, and the beneficial effects are as follows:

[0026] 1. The coating of the present invention is specially designed for equipment with high requirements for weather resistance and antifouling, and contains fluorocarbon resin, silicone modified acrylic resin, C8-18 fluoroalcohol phosphate, C30-45 alkyldimethylsilyl polypropylsilsesquioxane, aminosilane coupling agent, cyclopentasiloxane, lignin nanopowder, titanium dioxide, zinc phosphate, talc, silicon micropowder, leveling agent, defoamer, dispersant, ultraviolet absorber, antioxidant, propylene glycol methyl ether acetate and other ingredients. The ingredients are used in a certain proportion, and have excellent adhesion, wear resistance, weather resistance and antifouling, and can effectively extend the service life of the equipment and reduce the maintenance and repair frequency and cost.

[0027] 2. C8-18 fluoroalcohol phosphate can evenly disperse solid particles such as pigments and fillers in the coating system, prevent particle agglomeration, and improve the stability and uniformity of the coating. Ensure that the coating can be evenly applied to the surface of wind power equipment during construction to form a uniform coating, thereby improving the appearance quality and protective performance of the coating. C8-18 fluoroalcohol phosphate can reduce the surface tension of the coating, allowing the coating to better wet the surface of the wind power equipment and improve the adhesion of the coating. This is very important for large structural parts such as wind power equipment that are exposed to outdoor environments for a long time, and can ensure that the coating is firmly attached to the surface of the equipment and is not easy to fall off. The fluorinated groups it contains have low surface energy, which can make the coating surface resistant to dirt and not easily attached to pollutants such as dust and oil. Even if pollutants are attached, they can be easily washed away by rain, etc., keeping the surface of the equipment clean and reducing the maintenance cost of the equipment.

[0028] 3. The polypropyl silsesquioxane structure in C30-45 alkyldimethylsilyl polypropyl silsesquioxane has good thermal stability and chemical stability, and can resist the erosion of the coating by factors such as ultraviolet rays, temperature changes, and oxygen, thereby improving the weather resistance of the coating. In the outdoor environment where wind power equipment is located, it can ensure that the coating maintains good performance for a long time and prolong the service life of the coating. The presence of alkyldimethylsilyl groups makes the component highly hydrophobic, which can reduce the surface energy of the coating and make it difficult for water to adhere to and penetrate the surface of the coating. This helps prevent moisture from corroding wind power equipment and improves the anti-corrosion performance of the equipment. It can also increase the hardness, wear resistance and scratch resistance of the coating, so that the coating can resist the scouring and wear of wind, sand, rain, etc., and protect the surface of wind power equipment from mechanical damage.

[0029] Fourth, lignin nanopowder has a high specific surface area and strength, and can form a good interface with the polymer matrix in the coating, enhance the mechanical properties of the coating, and improve the tensile strength, compressive strength and toughness of the coating. This can ensure the integrity and protective performance of the coating when wind power equipment is subjected to wind, vibration and other forces in a complex outdoor environment. Lignin has a certain ability to absorb ultraviolet rays, which can reduce the damage of ultraviolet rays to the coating and improve the weather resistance of the coating. When wind power equipment is exposed to sunlight for a long time, it can reduce the aging effect of ultraviolet rays on the coating and extend the service life of the coating.

[0030] 5. C8-18 fluoroalcohol phosphate and C30-45 alkyldimethylsilyl polypropyl silsesquioxane have good compatibility. The low surface energy characteristics of C8-18 fluoroalcohol phosphate combined with the hydrophobic effect of C30-45 alkyldimethylsilyl polypropyl silsesquioxane can further reduce the surface energy of the coating, making the coating have better anti-fouling performance. Pollutants are difficult to adhere to the surface of the coating. Even if a small amount of pollutants are attached, they are easier to remove, keeping the surface of the wind power equipment clean. The anti-ultraviolet and antioxidant properties of fluoroalcohol phosphates work together with the thermal stability and chemical stability of polypropyl silsesquioxane, which can more effectively resist the erosion of the coating by various factors in the outdoor environment and greatly improve the weather resistance of the coating. The coating of the wind power equipment is not prone to fading, powdering, peeling, etc. during long-term use, maintaining a good appearance and protective performance. The dispersing effect of fluoroalcohol phosphate can make polypropyl silsesquioxane better dispersed in the coating system, avoid its agglomeration and precipitation, and improve the stability and uniformity of the coating. At the same time, the combined effect of the two can reduce the viscosity of the paint, improve the fluidity of the paint, make the paint easier to apply during the construction process, and form a uniform and smooth coating.

[0031] 6. C8-18 fluoroalcohol phosphate and lignin nanopowder have good compatibility. The dispersant effect of fluoroalcohol phosphate can help lignin nanopowder to be better dispersed in the coating system, prevent the agglomeration of lignin nanopowder, and improve the dispersion stability of lignin nanopowder in the coating. This helps to give full play to the reinforcing effect and other performance advantages of lignin nanopowder, making the performance of the coating more uniform and stable. The anti-ultraviolet and antioxidant properties of fluoroalcohol phosphate combined with the anti-ultraviolet properties of lignin nanopowder can more effectively resist the aging effect of ultraviolet rays and oxygen on the coating and improve the anti-aging properties of the coating. Extend the service life of the coating of wind power equipment and reduce the maintenance and replacement frequency of the coating. The synergistic effect of the two can comprehensively play their respective advantages, so that the coating has been significantly improved in terms of adhesion, weather resistance, wear resistance, and anti-fouling properties.

[0032] 7. Fluorocarbon resin can enable the coating to maintain good performance when exposed to outdoor environment for a long time, and it is not easy to fade, powder, crack and other phenomena, thus extending the service life of the coating; it has high tolerance to chemical substances such as acid, alkali, and salt, protecting the coated objects from chemical corrosion, and can firmly adhere to the surface of various substrates; the surface energy is low, and it is not easy to absorb pollutants such as dust and oil, so that the coating has a certain self-cleaning function to keep the surface clean.

[0033] Silicone-modified acrylic resin enhances the weather resistance and heat resistance of acrylic resin, enabling it to maintain good performance under relatively harsh environmental conditions, and increases the physical and mechanical properties of the coating, such as hardness, flexibility, and wear resistance, making the coating more durable and able to resist external mechanical wear and impact; it can maintain the gloss and color stability of the coating, and it is not easy to lose gloss or discolor after long-term use.

[0034] As an adhesion promoter, aminosilane coupling agent can enhance the bonding between the coating and the substrate, especially for inorganic substrates such as glass, metal, and ceramics, significantly improving the adhesion strength of the coating and preventing the coating from falling off. As a cross-linking agent, it reacts with the resin in the coating to form a three-dimensional network structure, improving the hardness, strength, and chemical resistance of the coating. By increasing the bonding strength between the coating and the substrate and the cross-linking density of the coating, the water resistance and weather resistance of the coating are improved, and the service life of the coating is extended.

[0035] Cyclopentasiloxane can reduce the surface tension of the coating, making it easier for the coating to level during construction, forming a smooth and even coating, reducing surface defects and improving the appearance quality of the coating. It can also reduce the friction resistance of the coating during construction, making it easier to apply the coating and improving construction efficiency.

[0036] Titanium dioxide has good weather resistance and is not easy to change color or fade under long-term light and climate change, and can maintain the color stability of the coating. It is not easy to react with other ingredients in the coating, ensuring the stability and reliability of the coating.

[0037] Zinc phosphate plays an anti-rust and anti-corrosion role in coatings. It can react with the metal surface to form a dense passivation film, which prevents oxygen, moisture and other corrosive substances from corroding the metal and protects the metal substrate.

[0038] Talc can improve the rheology and construction performance of the coating, making it easier to apply and improving construction efficiency, and can reduce sagging and dripping during construction. It helps to improve the flatness and smoothness of the coating, making the coating surface more delicate and reducing surface roughness. It has a certain wear resistance, which can improve the wear resistance of the coating and extend the service life of the coating.

[0039] Silica powder can improve the hardness and strength of the coating, making the coating more durable and resistant to external mechanical wear and impact. It has good wear resistance and increases the wear resistance of the coating. It can improve the crack resistance of the coating, reduce cracks in the coating during drying and use, and improve the integrity and stability of the coating.

[0040] 8. Mix the lignin nanopowder and C8-18 fluoroalcohol phosphate to make the lignin nanopowder fully infiltrate the C8-18 fluoroalcohol phosphate, evacuate and let stand to obtain a mixture B; the C8-18 fluoroalcohol phosphate can fully impregnate the surface and pores of the lignin nanopowder particles, improve the dispersibility of the lignin nanopowder and the compatibility with other ingredients, make it easier to disperse, improve the homogeneity of the coating, and prevent it from agglomerating and settling, thereby improving the coating performance of the coating, thereby improving various indicators and improving the protectiveness of the coating. DETAILED DESCRIPTION

[0041] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.

[0042] Example 1

[0043] A weather-resistant and anti-fouling topcoat for wind power equipment, the coating comprising the following raw materials in parts by mass: 35 parts of fluorocarbon resin, 35 parts of silicone-modified acrylic resin, 2.5 parts of C8-18 fluoroalcohol phosphate, 4 parts of C30-45 alkyldimethylsilylpolypropylsilsesquioxane, 2 parts of aminosilane coupling agent, 4 parts of cyclopentasiloxane, 1.2 parts of lignin nanopowder, 18 parts of titanium dioxide, 7.5 parts of zinc phosphate, 7 parts of talc, 5 parts of silicon micropowder, 0.8 parts of leveling agent, 1 part of defoaming agent, 0.8 parts of dispersant, 0.7 parts of ultraviolet absorber, 0.7 parts of antioxidant and 25 parts of propylene glycol methyl ether acetate.

[0044] The above-mentioned method for preparing a weather-resistant and anti-fouling topcoat for wind power equipment comprises the following steps:

[0045] S1: mixing zinc phosphate, talcum powder and silicon powder uniformly by air flow according to their weight proportions to obtain mixed powder A;

[0046] S2: Mixing lignin nanopowder and C8-18 fluoroalcohol phosphate according to mass fractions, so that the lignin nanopowder is fully infiltrated with C8-18 fluoroalcohol phosphate, and vacuuming and standing for 15 minutes to obtain a mixture B;

[0047] S3: Add leveling agent, defoaming agent, dispersant, UV absorber and antioxidant to propylene glycol methyl ether acetate in proportions by mass, mix at 2000 r / min for 18 min, then add titanium dioxide, mix at 1200 r / min for 18 min, then add fluorocarbon resin and silicone modified acrylic resin, mix at 900 r / min for 25 min, then add mixed powder A, mix at 900 r / min for 18 min, then add mixture B, C30-45 alkyldimethylsilylpolypropylsilsesquioxane and cyclopentasiloxane, mix at 900 r / min for 12 min, finally add aminosilane coupling agent, mix at 900 r / min for 12 min, to obtain coating.

[0048] Example 2

[0049] A weather-resistant and anti-fouling topcoat for wind power equipment, the coating comprising the following raw materials in parts by mass: 30 parts of fluorocarbon resin, 20 parts of silicone-modified acrylic resin, 2 parts of C8-18 fluoroalcohol phosphate, 3 parts of C30-45 alkyldimethylsilylpolypropylsilsesquioxane, 1 part of aminosilane coupling agent, 3 parts of cyclopentasiloxane, 1 part of lignin nanopowder, 15 parts of titanium dioxide, 5 parts of zinc phosphate, 5 parts of talc, 3 parts of silicon micropowder, 0.5 part of leveling agent, 0.5 part of defoaming agent, 0.5 part of dispersant, 0.5 part of ultraviolet absorber, 0.5 part of antioxidant and 20 parts of propylene glycol methyl ether acetate.

[0050] The above-mentioned method for preparing a weather-resistant and anti-fouling topcoat for wind power equipment comprises the following steps:

[0051] S1: mixing zinc phosphate, talcum powder and silicon powder uniformly by air flow according to their weight proportions to obtain mixed powder A;

[0052] S2: Mixing lignin nanopowder and C8-18 fluoroalcohol phosphate according to mass fractions, so that the lignin nanopowder is fully infiltrated with C8-18 fluoroalcohol phosphate, and vacuuming and standing for 10 minutes to obtain a mixture B;

[0053] S3: Add leveling agent, defoaming agent, dispersant, UV absorber and antioxidant to propylene glycol methyl ether acetate in proportions by mass, mix at 1500 r / min for 15 min, then add titanium dioxide, mix at 1000 r / min for 15 min, then add fluorocarbon resin and silicone modified acrylic resin, mix at 800 r / min for 20 min, then add mixed powder A, mix at 800 r / min for 15 min, then add mixture B, C30-45 alkyldimethylsilylpolypropylsilsesquioxane and cyclopentasiloxane, mix at 800 r / min for 10 min, finally add aminosilane coupling agent, mix at 800 r / min for 10 min, to obtain coating.

[0054] Example 3

[0055] A weather-resistant and anti-fouling topcoat for wind power equipment, the coating comprising the following raw materials in parts by mass: 32 parts of fluorocarbon resin, 22 parts of silicone-modified acrylic resin, 2.2 parts of C8-18 fluoroalcohol phosphate, 3.5 parts of C30-45 alkyldimethylsilylpolypropylsilsesquioxane, 1.5 parts of aminosilane coupling agent, 3.5 parts of cyclopentasiloxane, 1.1 parts of lignin nanopowder, 16 parts of titanium dioxide, 6 parts of zinc phosphate, 6 parts of talc, 4 parts of silicon micropowder, 0.6 parts of leveling agent, 0.7 parts of defoaming agent, 0.6 parts of dispersant, 0.6 parts of ultraviolet absorber, 0.6 parts of antioxidant and 22 parts of propylene glycol methyl ether acetate.

[0056] The above-mentioned method for preparing a weather-resistant and anti-fouling topcoat for wind power equipment comprises the following steps:

[0057] S1: mixing zinc phosphate, talcum powder and silicon powder uniformly by air flow according to their weight proportions to obtain mixed powder A;

[0058] S2: Mixing lignin nanopowder and C8-18 fluoroalcohol phosphate according to mass fractions, so that the lignin nanopowder is fully infiltrated with C8-18 fluoroalcohol phosphate, and vacuuming and standing for 10 minutes to obtain a mixture B;

[0059] S3: Add leveling agent, defoaming agent, dispersant, UV absorber and antioxidant to propylene glycol methyl ether acetate in proportions by mass, mix at 1800 r / min for 15 min, then add titanium dioxide, mix at 1100 r / min for 15 min, then add fluorocarbon resin and silicone modified acrylic resin, mix at 800 r / min for 20 min, then add mixed powder A, mix at 800 r / min for 15 min, then add mixture B, C30-45 alkyldimethylsilylpolypropylsilsesquioxane and cyclopentasiloxane, mix at 800 r / min for 10 min, finally add aminosilane coupling agent, mix at 800 r / min for 10 min to obtain coating.

[0060] Example 4

[0061] A weather-resistant and anti-fouling topcoat for wind power equipment, the coating comprising the following raw materials in parts by mass: 38 parts of fluorocarbon resin, 28 parts of silicone-modified acrylic resin, 2.8 parts of C8-18 fluoroalcohol phosphate, 4.5 parts of C30-45 alkyldimethylsilylpolypropylsilsesquioxane, 2.5 parts of aminosilane coupling agent, 4.5 parts of cyclopentasiloxane, 1.4 parts of lignin nanopowder, 19 parts of titanium dioxide, 9 parts of zinc phosphate, 9 parts of talc, 7 parts of silicon micropowder, 0.8 parts of leveling agent, 1.3 parts of defoaming agent, 0.9 parts of dispersant, 0.8 parts of ultraviolet absorber, 0.9 parts of antioxidant and 28 parts of propylene glycol methyl ether acetate.

[0062] The above-mentioned method for preparing a weather-resistant and anti-fouling topcoat for wind power equipment comprises the following steps:

[0063] S1: mixing zinc phosphate, talcum powder and silicon powder uniformly by air flow according to their weight proportions to obtain mixed powder A;

[0064] S2: Mixing lignin nanopowder and C8-18 fluoroalcohol phosphate according to mass fractions, so that the lignin nanopowder is fully infiltrated with C8-18 fluoroalcohol phosphate, and vacuuming and standing for 20 minutes to obtain a mixture B;

[0065] S3: Add leveling agent, defoaming agent, dispersant, UV absorber and antioxidant to propylene glycol methyl ether acetate in proportions by mass, mix at 2300 r / min for 20 min, then add titanium dioxide, mix at 1400 r / min for 20 min, then add fluorocarbon resin and silicone modified acrylic resin, mix at 1000 r / min for 20 min, then add mixed powder A, mix at 1000 r / min for 15 min, then add mixture B, C30-45 alkyldimethylsilylpolypropylsilsesquioxane and cyclopentasiloxane, mix at 1000 r / min for 10 min, finally add aminosilane coupling agent, mix at 1000 r / min for 10 min to obtain coating.

[0066] Example 5

[0067] A weather-resistant and anti-fouling topcoat for wind power equipment, the coating comprising the following raw materials in parts by mass: 40 parts of fluorocarbon resin, 30 parts of silicone-modified acrylic resin, 3 parts of C8-18 fluoroalcohol phosphate, 5 parts of C30-45 alkyldimethylsilylpolypropylsilsesquioxane, 3 parts of aminosilane coupling agent, 5 parts of cyclopentasiloxane, 1.5 parts of lignin nanopowder, 20 parts of titanium dioxide, 10 parts of zinc phosphate, 10 parts of talc, 8 parts of silicon micropowder, 1 part of leveling agent, 1.5 parts of defoaming agent, 1 part of dispersant, 1 part of ultraviolet absorber, 1 part of antioxidant, and 30 parts of propylene glycol methyl ether acetate.

[0068] The above-mentioned method for preparing a weather-resistant and anti-fouling topcoat for wind power equipment comprises the following steps:

[0069] S1: mixing zinc phosphate, talcum powder and silicon powder uniformly by air flow according to their weight proportions to obtain mixed powder A;

[0070] S2: Mixing lignin nanopowder and C8-18 fluoroalcohol phosphate according to mass fractions, so that the lignin nanopowder is fully infiltrated with C8-18 fluoroalcohol phosphate, and vacuuming and standing for 20 minutes to obtain a mixture B;

[0071] S3: Add leveling agent, defoaming agent, dispersant, UV absorber and antioxidant to propylene glycol methyl ether acetate in proportions by mass, mix at 2500 r / min for 20 min, then add titanium dioxide, mix at 1500 r / min for 20 min, then add fluorocarbon resin and silicone modified acrylic resin, mix at 1000 r / min for 30 min, then add mixed powder A, mix at 1000 r / min for 20 min, then add mixture B, C30-45 alkyldimethylsilylpolypropylsilsesquioxane and cyclopentasiloxane, mix at 1000 r / min for 15 min, finally add aminosilane coupling agent, mix at 1000 r / min for 15 min to obtain coating.

[0072] In the above embodiments: the model of fluorocarbon resin is ZHM-2, which is sourced from Shandong Moore Chemical Co., Ltd. The model of organosilicon-modified acrylic resin is SJ-106, which is sourced from Congyang County Sanjin Pigment Co., Ltd. C8-18 fluoroalcohol phosphate and C30-45 alkyldimethylsilyl polypropylsilsesquioxane are sourced from Green Yi (Guangzhou) Technology Service Co., Ltd. The model of aminosilane coupling agent is KH-550, which is sourced from Guangzhou Zhongjie Chemical Technology Co., Ltd. The model of cyclopentadimethylsiloxane is IOTAD5, which is sourced from Anhui Aiyota Silicone Oil Co., Ltd. The particle size range of lignin nanopowder is less than 1 μm, which is sourced from Shandong Gaotang Multi-Lignin Co., Ltd. The particle size range of titanium dioxide is 10 μm to 300 μm. The particle size range of zinc phosphate is less than 10 μm. The particle size range of talc is less than 10 μm. The particle size range of silicon micropowder is 0.5 um to 50 μm. The leveling agent is a polyurethane leveling agent, model 2041, from Laiyang Shengbang Silicone Technology Co., Ltd. The defoamer model is DF-2409, from Dongguan Defeng Defoamer Co., Ltd.; the dispersant model is DH-5038, from Suzhou Qingtian New Materials Co., Ltd.; the ultraviolet absorber model is UV-1, from Dongguan Shanyi Plastic Co., Ltd.; the antioxidant is antioxidant 1010, from Shanghai Kaizhi New Materials Technology Co., Ltd. Propylene glycol methyl ether acetate is from Shandong Taiyu Chemical Co., Ltd.

[0073] Comparative Example 1

[0074] No C8-18 fluoroalcohol phosphate is added to the coating; other parameters and methods are the same as in Example 1.

[0075] Comparative Example 2

[0076] No C30-45 alkyldimethylsilylpolypropylsilsesquioxane was added to the coating; other parameters and methods were the same as in Example 1.

[0077] Comparative Example 3

[0078] Neither C8-18 fluoroalcohol phosphate nor C30-45 alkyldimethylsilylpolypropylsilsesquioxane is added to the coating; other parameters and methods are the same as those in Example 1.

[0079] Comparative Example 4

[0080] No lignin nanopowder is added to the coating; other parameters and methods are the same as in Example 1.

[0081] Comparative Example 5

[0082] Neither C8-18 fluoroalcohol phosphate nor lignin nanopowder is added to the coating; other parameters and methods are the same as in Example 1.

[0083] Comparative Example 6

[0084] In the preparation method, S2 does not prepare mixture B, that is, C8-18 fluoroalcohol phosphate and lignin nanopowder are not premixed. In S3, mixture B is directly replaced by C8-18 fluoroalcohol phosphate and lignin nanopowder. Other parameters and methods are the same as in Example 1.

[0085] The coatings prepared in the above-mentioned embodiments and comparative examples were tested for their performance.

[0086] Test plate: The substrate is a carbon steel plate, and the coating is: the primer is Hempel's epoxy zinc-rich primer 17360-19830, the primer coating thickness is 50 μm, and the topcoat is the coating of each embodiment and each comparative example, and the topcoat coating thickness is 100 μm. The steel plate scraping method is carried out in accordance with GB / T 1727 "General Preparation Method for Paint Film".

[0087] (1) According to GB / T 1728 "Determination of Drying Time of Paint Film and Putty Film" finger touch method, test the surface drying time of the topcoat coating;

[0088] (2) According to GB / T 9286 "Cross-cut test for paint and varnish film", the cross-cut method test is used to test adhesion: use a cross-cut tool to cut on the surface of the test plate with a cut-off distance of 2 mm; after cutting, tape is applied to the cut-off area, and then the tape is quickly removed to observe the shedding of the coating. The adhesion is rated according to the ratio of the shedding area of ​​the coating to the total cut-off area.

[0089] (3) According to GB / T 1733 "Determination of water resistance of paint film", test water resistance: put the test plate into deionized water, immerse 2 / 3 of the test plate in water, and keep the water temperature at 25℃; after 120 hours, observe whether the test plate has blistering, peeling, rusting, etc. Evaluation level: Level 1: The paint film is completely kept in its original state, and there is no loss of gloss, discoloration, blistering, wrinkling, peeling, rusting, etc. on the paint film; Level 2: There are slight changes on the surface of the paint film, such as slight loss of gloss and slight lightening of color, but it does not affect the overall performance and appearance of the paint film; Level 3: There are obvious changes on the surface of the paint film, such as obvious loss of gloss, discoloration, blistering, wrinkling, etc., but it has not reached the level of serious damage; Unqualified: The paint film has serious blistering, peeling, rusting, etc., and the water resistance of the paint film is very poor and cannot meet the use requirements.

[0090] (4) According to GBT 23988 “Determination of Abrasion Resistance of Coatings by Falling Sand Method”, the abrasion resistance is tested: the falling sand particle size range of the impact device is 0.3 mm to 1 mm, the impact height is 1000 mm, the impact number is 1000 times, and the wear coefficient is calculated.

[0091] (5) According to GB / T 23987 “Artificial weathering of paint and varnish coatings: exposure to fluorescent ultraviolet light and water”, artificial accelerated ultraviolet light aging test, testing weathering hydrophobicity and weathering adhesion: using UVA (340nm) light source, irradiance of 0.83W / m 2 , 60℃ illumination for 4 hours, 50℃ condensation for 4 hours, the test time is 3000 hours. After aging, the test panel coating is tested with a contact angle meter to calculate the surface energy change rate. UV weathering surface energy change rate = (surface energy after aging test - initial surface energy after drying) / initial surface energy after drying × 100%; the cross-hatch method is used to test the UV weathering adhesion level.

[0092] (6) According to GB / T 1865-2009 “Paints and varnishes - Artificial weathering and artificial radiation exposure to filtered xenon arc radiation”, xenon lamp aging test, test weathering hydrophobicity and weathering adhesion: Place the test panel in a xenon lamp aging test chamber, control the irradiance at a wavelength of 340nm, and the irradiance setting value is 0.51W / m 2 The blackboard temperature is set at 65℃, the temperature in the test box is 50℃ during the light stage; the temperature is 20℃ during the dark stage, and the relative humidity is 55%. The rainfall time is 15min, the rain stop time is 2h, the water spray pressure of the rainfall is controlled at 0.15MPa, and the rainfall water quality is distilled water. The test time is 2000 hours. After aging, the test board coating is tested using a contact angle meter to calculate the surface energy change rate, radiation weathering surface energy change rate = (surface energy after aging test-initial surface energy after drying) / initial surface energy after drying × 100%; the cross-hatch method is used to test the radiation weathering adhesion level.

[0093] (7) Anti-fouling test: Apply muddy water evenly on the surface of the test plate, but do not apply too much to cause muddy water to flow. Place the test plate in an environment with a temperature of 25°C and a relative humidity of 55%. The residence time of the pollutants on the surface of the test plate is 12 hours; use deionized water and a rag to clean for 5 minutes; use uniform force during cleaning to avoid damaging the paint on the surface of the test plate. After cleaning, use the naked eye and a magnifying glass to carefully observe the surface of the test plate to see if there are any pollutants, paint discoloration, coating damage or peeling. Evaluation: If there are almost no pollutants on the surface of the test plate, and the paint color and coating state have not changed significantly, the anti-fouling performance is excellent; if there are a small amount of pollutants, but they can be removed by simple cleaning methods, and the paint color and coating state have basically not changed, the anti-fouling performance is good; if there are more pollutants, a stronger cleaning method is required to remove them, or the paint color and coating state have changed significantly, the anti-fouling performance is qualified; if the pollutants cannot be removed, or the paint has serious discoloration, damage, peeling, etc., the anti-fouling performance is unqualified.

[0094] The test results of the embodiment are shown in Table 1 below.

[0095] Table 1 Example coating performance test results

[0096]

[0097] It can be seen from the above results that the coatings of Examples 1 to 5 have good adhesion, water resistance, wear resistance, weather resistance and anti-fouling properties, and can effectively extend the service life of wind power equipment and reduce maintenance frequency and maintenance costs.

[0098] The test results of the comparative example are shown in Table 2 below.

[0099] Table 2 Comparative Example Coating Performance Test Results

[0100]

[0101]

[0102] It can be seen from the above results that the coating performance of the comparative examples has declined. From the results of comparative example 1, it can be seen that C8-18 fluoroalcohol phosphate can improve the stability and uniformity of the coating, reduce the surface tension of the coating, and improve the adhesion of the coating; the fluorinated groups contained therein have lower surface energy, which can make the coating surface anti-fouling and not easy to be attached by pollutants such as dust; without adding C8-18 fluoroalcohol phosphate, the wear resistance and weather resistance of the topcoat coating are poor, especially the weather resistance adhesion grade is significantly reduced. From the results of Comparative Example 2, it can be seen that the polypropyl silsesquioxane structure in the C30-45 alkyldimethylsilyl polypropyl silsesquioxane has good thermal stability and chemical stability, can resist the erosion of the coating by factors such as ultraviolet rays, temperature changes, and oxygen, and improves the weather resistance of the coating; the presence of the alkyldimethylsilyl group makes the component have strong hydrophobicity and anti-fouling properties, can reduce the surface energy of the coating, and make it difficult for water and mud to adhere to and penetrate the surface of the coating; it can also increase the wear resistance and scratch resistance of the coating, so that the coating can resist scouring and wear by wind, sand, rain, etc.; without adding C30-45 alkyldimethylsilyl polypropyl silsesquioxane, the water resistance, wear resistance, weather resistance and anti-fouling properties of the coating are reduced. From the results of Comparative Example 3, it can be seen that C8-18 fluoroalcohol phosphate and C30-45 alkyldimethylsilylpolypropylsilsesquioxane have a good synergistic effect: the low surface energy characteristics of C8-18 fluoroalcohol phosphate combined with the hydrophobic effect of C30-45 alkyldimethylsilylpolypropylsilsesquioxane can further reduce the surface energy of the coating, so that the coating has better anti-fouling performance; the anti-ultraviolet and antioxidant properties of fluoroalcohol phosphate and the thermal stability and chemical stability of polypropylsilsesquioxane cooperate with each other, which can more effectively resist the erosion of the coating by various factors in the outdoor environment, and greatly improve the weather resistance of the coating; the dispersing effect of fluoroalcohol phosphate can make polypropylsilsesquioxane better dispersed in the coating system, thereby improving the stability and uniformity of the coating. Failure to add C8-18 fluoroalcohol phosphate and C30-45 alkyldimethylsilylpolypropylsilsesquioxane will affect the homogeneity of the coating, resulting in the coating's performance being affected, the adhesion being reduced, more pollutants remaining, difficult cleaning, and reduced antifouling grade, weather resistance, etc. From the results of Comparative Example 4, it can be seen that lignin nanopowder has a high specific surface area and strength, can form a good interface bond with the polymer matrix in the coating, and ensure the integrity and protective performance of the coating; lignin has a certain ability to absorb ultraviolet rays, can reduce the damage of ultraviolet rays to the coating, and improve the weather resistance of the coating.From the results of comparative example 5, it can be seen that C8-18 fluoroalcohol phosphate and lignin nanopowder have a good coordination effect. The dispersant effect of fluoroalcohol phosphate can help lignin nanopowder to be better dispersed in the coating system, prevent the agglomeration of lignin nanopowder, improve the dispersion stability of lignin nanopowder in the coating, and make the performance of the coating more uniform and stable; the anti-ultraviolet and antioxidant properties of fluoroalcohol phosphate combined with the anti-ultraviolet properties of lignin nanopowder can more effectively resist the aging effect of ultraviolet rays and oxygen on the coating, and improve the anti-aging performance of the coating; the synergistic effect of the two can comprehensively play their respective advantages, so that the coating is significantly improved in terms of adhesion, weather resistance, wear resistance, antifouling, etc. From the results of comparative example 6, it can be seen that if C8-18 fluoroalcohol phosphate and lignin nanopowder are not pre-mixed, it will affect the particle permeability of C8-18 fluoroalcohol phosphate in lignin nanopowder, reduce the dispersibility of lignin nanopowder, and compatibility with other ingredients, thereby affecting the homogeneity of the coating and affecting the decline of indicators.

Claims

1. A weather-resistant and anti-fouling topcoat for wind power equipment, characterized in that: The coating includes the following raw materials in parts by mass: 30 to 40 parts of fluorocarbon resin, 20 to 30 parts of silicone modified acrylic resin, 2 to 3 parts of C8-18 fluoroalcohol phosphate, 3 to 5 parts of C30-45 alkyldimethylsilylpolypropylsilsesquioxane, 1 to 3 parts of aminosilane coupling agent, 3 to 5 parts of cyclopentasiloxane, 1 to 1.5 parts of lignin nanopowder, 15 to 20 parts of titanium dioxide, 5 to 10 parts of zinc phosphate, 5 to 10 parts of talc, 3 to 8 parts of silicon micropowder, 0.5 to 1 part of leveling agent, 0.5 to 1.5 parts of defoaming agent, 0.5 to 1.5 parts of dispersant, 0.5 to 1 part of ultraviolet absorber, 0.5 to 1 part of antioxidant, and 20 to 30 parts of propylene glycol methyl ether acetate.

2. A weather-resistant and anti-fouling topcoat for wind power equipment according to claim 1, characterized in that: The particle size range of the lignin nano powder is below 1 μm.

3. The weather-resistant and anti-fouling topcoat for wind power equipment according to claim 1, characterized in that: The particle size of the titanium dioxide is in the range of 10 μm to 300 μm.

4. The weather-resistant and anti-fouling topcoat for wind power equipment according to claim 1, characterized in that: The particle size of the zinc phosphate is below 10 μm.

5. The weather-resistant and anti-fouling topcoat for wind power equipment according to claim 1, characterized in that: The particle size of the talc powder is less than 10 μm.

6. The weather-resistant and anti-fouling topcoat for wind power equipment according to claim 1, characterized in that: The particle size of the silicon micropowder ranges from 0.5 μm to 50 μm.

7. The weather-resistant and anti-fouling topcoat for wind power equipment according to claim 1, characterized in that: The leveling agent is a polyurethane leveling agent, model 2041; the defoaming agent is model DF-2409; the dispersant is model DH-5038; the ultraviolet absorber is model UV-1; and the antioxidant is antioxidant 1010.

8. A method for preparing a weather-resistant and anti-fouling topcoat for wind power equipment, used for preparing a weather-resistant and anti-fouling topcoat for wind power equipment according to claim 1, characterized in that: The preparation method comprises the following steps: S1: Mix zinc phosphate, talcum powder and silica powder uniformly by air flow according to their weight proportions to obtain mixed powder A; S2: Mixing lignin nanopowder and C8-18 fluoroalcohol phosphate according to mass fractions, so that the lignin nanopowder is fully infiltrated with C8-18 fluoroalcohol phosphate, and vacuuming and standing for 10 min to 20 min to obtain a mixture B; S3: Add leveling agent, defoamer, dispersant, UV absorber and antioxidant to propylene glycol methyl ether acetate according to mass fractions, mix at 1500r / min~2500r / min for 15min~20min, then add titanium dioxide, mix at 1000r / min~1500r / min for 15min~20min, then add fluorocarbon resin and silicone modified acrylic resin, mix at 800r / min~1000r / min for 20min~30min. min, then add mixed powder A, mix at 800r / min~1000r / min for 15min~20min, then add mixture B, C30-45 alkyldimethylsilylpolypropylsilsesquioxane and cyclopentasiloxane, mix at 800r / min~1000r / min for 10min~15min, finally add aminosilane coupling agent, mix at 800r / min~1000r / min for 10min~15min to obtain coating.

Citation Information

Patent Citations

  • Finish paint for wind driven generator and preparation method thereof

    CN102127363A

  • Environment-friendly paint for metal doors and windows and preparation method of paint

    CN108485518A

  • stabilization of the polyethylene latexes and latexes thus obtained

    FR1324487A

  • Compositions containing an acrylic film former, a tackifier and an ester

    US20140242014A1